TRIBOLOGICAL PROPERTIES OF HYBRID COMPOSITES BASED ON WOVEN CARBON FIBER/FINE KENAF FABRIC REINFORCED EPOXY MATRIX FOR AUTOMOTIVE APPLICATION - Sarifuddin, Norshahida (2020)
The demand for a combination of materials that satisfy the requirements of the world market has been exponentially growing in recent years. It is predicted that the upcoming years will guarantee a significant evolution of new classification of hybrid composite materials. The exploration of applicable alternatives to minimize the usage of synthetic fibers have led to the concepts of using both kinds of fibers as reinforcements to thermoset polymers. These highlight the fact that kenaf fibers are an emerging partial substitute to carbon fibers as reinforcements in polymer composites. Despite this interest, limited attention has been devoted to the quality of textile architecture of kenaf fabrics which eventually affects the overall properties of the laminated composites. The true challenge is to obtain more balanced properties in the fabric plane which can be achieved by appropriate fiber-matrix adhesion. Hence, using appropriate fabrication techniques the fundamental mechanisms of hybrid composites under different processing parameters and loading conditions may be understood and determined. In this work, interlacing layer hybrid composites were fabricated using vacuum infusion technique at which woven carbon and kenaf fibres were used as reinforcing agents with epoxy matrix. The volume fraction of fibre and thickness of hybrid composites varied from 40 vol.% to 50 vol.% and 3mm to 5 mm, respectively. In addition, four different sequences (CCCCC, KKKKK, KCKCK, CKCKC) were introduced. Mechanical testing including tensile test and flexural test were carried out according to ASTM D3039 and ASTM D790, respectively. Scanning Electron Microscope and Optical Microscope were used to determine the mode of failures in both tensile and flexural tests of carbon/kenaf hybrid composites. The optimization of mechanical properties was done using Design of Expert (DOE). Consequently, dry sliding wear and friction test was performed using Pin-On-Disc Tester. Under sliding conditions (applied loads and sliding speeds), the composite parameters (stacking sequences and compositions) greatly affected the tribological properties (coefficient of friction and wear rate) of these types of hybrid composites.